Functional growth analysis of diploid potato cultivars (Solanum phureja Juz. et Buk.) (2020)
Plant growth analysis has been widely used to study factors that influence plant growth. This analysis uses a set of quantitative methods that describe and analyze the growth of plants and their organs. It uses data from direct measurements (weight, area, volume) and quantifies and analyzes growth using indexes based on models defined by mathematical functions. This study conducted a functional growth analysis of diploid potato cultivars in Colombia. The functional growth analysis of diploid potato cultivars was carried out over three consecutive growing seasons in Medellín, Colombia. A randomized block design was used with two levels of fertilization and five repetitions. The first factor corresponded to the three potato cultivars, and the second factor was two fertilization levels: 260 and 778 kg of fertilizer per hectare. Samples were taken weekly, and each sample was an entire plant per experiment unit. The dry weight of each organ and the leaf area were measured. These measurements were used to calculate the relative growth rate, leaf area ratio, net assimilation rate, and specific leaf area. The development time was evaluated in accumulated degree-days with threshold temperatures of 2 and 29°C. The three cultivars recorded their highest net assimilation rate at 1,252 accumulated degree days (ADD), with values of 0.0002565, 0.0002021, and 0.0001778 g cm-2 ADD-1 in the ‘Latina’, ‘Guaneña’, and ‘Colombia’ cultivars, respectively. The Latina cultivar stood out in several physiological characteristics, including the fastest developing cultivar. ‘Latina’ also had the highest total dry mass accumulated in the cycle (271.05 g) and accumulated dry matter in tubers (237 g).